2006
DOI: 10.14411/eje.2006.006
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive preferential selection of female coccinellid hosts by the parasitoid wasp Dinocampus coccinellae (Hymenoptera: Braconidae)

Abstract: Abstract. Females of the parasitoid wasp Dinocampus coccinellae are known to parasitise both male and female coccinellid hosts. It is suggested that female hosts provide more resources for developing wasp larvae because they tend to be larger than male hosts, and female coccinellids have a much greater food intake than males. Thus the wasp's lifetime reproductive success should be increased by ovipositing preferentially in female rather than male hosts when given a choice. Laboratory experiments, using Coccine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 20 publications
0
23
0
Order By: Relevance
“…It was noted by several authors (Maeta 1969, Parker et al 1977, Cartwright et al 1982 ) that female ladybirds are parasitized to a higher degree than males, and Davis et al (2006) confi rmed experimentally the preference of British D. coccinellae for ovipositing into female rather than male C. septempunctata hosts. Moreover, British D. coccinellae , having a choice between young (newly eclosed) and old (overwintered) C. septempunctata adults, oviposited preferentially into young ones.…”
Section: Host P References and P Arasitization R Atesmentioning
confidence: 63%
“…It was noted by several authors (Maeta 1969, Parker et al 1977, Cartwright et al 1982 ) that female ladybirds are parasitized to a higher degree than males, and Davis et al (2006) confi rmed experimentally the preference of British D. coccinellae for ovipositing into female rather than male C. septempunctata hosts. Moreover, British D. coccinellae , having a choice between young (newly eclosed) and old (overwintered) C. septempunctata adults, oviposited preferentially into young ones.…”
Section: Host P References and P Arasitization R Atesmentioning
confidence: 63%
“…One of the best understood parasitoids is Dinocampus (Perilitus) coccinellae Schrank (Hymenoptera: Braconidae), whose host preference, life history, ecology, and behavior have been thoroughly investigated (Ceryngier and Hodek, 1996;Majerus et al, 2000a;Okuda and Ceryngier, 2000;Al Abassi et al, 2001;Davis et al, 2006;Firlej et al, 2006;Koyama and Majerus, 2008). Adult coccinellids are preferred, especially older females (Majerus et al, 2000a;Davis et al, 2006), but immature parasitoids have been found in host larvae and pupae (Geoghegan et al, 1998). As a solitary endoparasitoid of adults, D. coccinellae prefers larger species of Coccinellinae (Ceryngier and Hodek, 1996).…”
Section: Hymenopterous Parasitoids Of Entomophagous Coccinellidsmentioning
confidence: 99%
“…Within a host species, field prevalence levels are higher in females than males (Maeta 1969;Parker et al 1977;Cartwright et al 1982). In laboratory tests, Davis et al (2006) showed that female D. coccinellae have a preference to oviposit into female rather than male adults of C. septempunctata, and that this preference was in addition to the preference the wasp shows for larger hosts in choice tests. As female coccinellids eat more than males (Hodek 1996;Dixon 2000), Davis et al (2006) argue that this preference is adaptive, providing developing wasp larvae with increased resources.…”
Section: Introductionmentioning
confidence: 99%